Antara Tradisi dan Inovasi: Menelisik Ustadzah Halimah Alaydrus dalam Dakwah Digital - Jum'ah, Jum'ah; Muhammad Yazid; Lukmana, Lukmana (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
Da'wah is the act of inviting people to do good and avoid wrongdoing (amar ma'ruf nahi mungkar). Traditionally, mosques, prayer rooms, and similar settings have hosted lectures and gatherings for da'wah. However, as technology advances, da'wah has adapted to the digital age, with social media becoming an increasingly popular medium. Among the figures utilizing these platforms is Ustadzah Halimah Alaydrus, who actively employs YouTube and Instagram to reach a broader audience, particularly Muslim women. As a prominent female Muslim figure, Ustadzah Halimah Alaydrus has embraced the opportunities offered by digital platforms to carry out da'wah in the modern era. This study examines two key aspects: the role of Ustadzah Halimah Alaydrus in digital da'wah and the strategies she employs to convey Islamic teachings through YouTube and Instagram. Using a qualitative approach with a descriptive research method, this study applies content analysis to explore the messages shared by Ustadzah Halimah Alaydrus on these platforms. The findings highlight her significant role in promoting digital da'wah, particularly in empowering Muslim women. Her efforts have had a positive impact on strengthening women's faith, expanding their knowledge, and improving their social awareness. What distinguishes her da'wah is the way she delivers her messages—thoughtfully crafted to inspire and resonate with the daily lives of Muslim women. Furthermore, her success in leveraging Instagram and YouTube lies in her ability to present engaging and creative content that effectively spreads Islamic values to a broader audience